Chicano Popular Culture, Second Edition : Que Hable el Pueblo - Tatum, Charles M. (Book collections on Project MUSE., 2017)
"An updated and expanded edition of Tatum's Chicano Popular Culture (2001), touching upon major developments in popular culture since the book's original publication"--Provided by publisher